Ocular setariasis in the anterior chamber of the eye of a horse: a case report - Roslim, Noorashimah; Mohd Adzahan, Noraniza; Ahmad Affandi, Syahirah; Rais, Mohamad Naguib; Awang Kamaludin, Dayang Norhaizum; Abdul Razak, Ismasyahir; Fateh Mohamed, Bashir Ahmad (2015)
Ocular setariasis is an ectopic parasitism by Setaria spp and transmitted by mosquitoes. A 10-year-old Arabian was referred to University Veterinary Hospital (UVH), Faculty of Veterinary Medicine, Universiti Putra Malaysia with primary complaint of intraocular parasite. Physical examination revealed presence of actively alive parasite in the anterior chamber on the right eye, cloudiness and opacity of the cornea. Upon examination, the horse showed signs of ocular pain, squinting, photophobia, lacrimation, blepharospasm and moderate conjunctivitis. Positive menace reflex was observed. Diagnosis was made based on visualization of the mobile parasite in the aqueous humour, however microfilaria was not detected in blood. The horse was treated medically with topical antibiotic (chloramphenicol ointment) as prophylaxis and to prevent superficial bacterial keratitis, non-steroidal anti-inflammatory drug (Flunixin meglumine, 1.1 mg/kg) to reduce intraocular inflammation, and atropine sulfate ophthalmic solution 1% to reduce intraocular pressure and reduce the degree of uveitis. Promectin® plus containing abamectin (3.7mg/g) and praziquantel (46.2mg/g) was given orally for antiparasitic agents. At 1-month post-treatment, there was no evidence of mobile parasite observed but ocular inflammation and opacity were prominent due to delayed absorption of dead parasite in anterior chamber. Prognosis for this case was poor due to development of anterior uveitis and blindness in horse. Surgical removal of parasite is the best option, where good prognosis can be achieved with shorter treatment period.